THE EFFECT OF MNEMONIC TECHNIQUE WITH CROSSWORD PUZZLE MEDIA IN TEACHING VOCABULARY: Pre-Experimental Research - Pratiwi, A. Yuniarti Dian; Latief, Hasnawati; Hamid, Radiah (FKIP Unismuh Makassar, 2018)
The thesis aimed at finding out the improvement of the students’ vocabulary at the 10th grade of SMA Negeri 11 Watampone in 2017/2018 Academic year in term of Mnemonic Technique with Crossword Puzzle Media. The researcher findings indicated that Mnemonic Technique with Crossword Puzzle Media effective could improve students’ vocabulary mastery. The result of the data indicated that, there was difference between students’ pre-test and post-test. The mean score of post-test (86, 11) was greater than the mean score of pre-test (69, 25). From t-test, the researcher found that, the value of t-test (7.082) was greater than t-table (2.056) at the level of significance 0. 05 with degree of freedom (df) = 27.result shows that t-test value for the final score of students’ vocabulary was (7.082 > 2.080). It means that there is significant difference between the students’ vocabulary mastery before and after using Mnemonic Technique with Crossword Puzzle Media. It is also said that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. Based on the finding and discussion of the research, the researcher concluded that, the using of Mnemonic Technique with Crossword Puzzle Media could improve the students’ vocabulary mastery at the 10th Grade of SMA Negeri 11 Watampone